2021
DOI: 10.1002/mrm.28887
|View full text |Cite
|
Sign up to set email alerts
|

Denoising of hyperpolarized 13C MR images of the human brain using patch‐based higher‐order singular value decomposition

Abstract: Purpose To improve hyperpolarized 13C (HP‐13C) MRI by image denoising with a new approach, patch‐based higher‐order singular value decomposition (HOSVD). Methods The benefit of using a patch‐based HOSVD method to denoise dynamic HP‐13C MR imaging data was investigated. Image quality and the accuracy of quantitative analyses following denoising were evaluated first using simulated data of [1‐13C]pyruvate and its metabolic product, [1‐13C]lactate, and compared the results to a global HOSVD method. The patch‐base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 48 publications
3
57
0
Order By: Relevance
“…The in vivo 13 C data were reconstructed and analyzed in MATLAB (MathWorks). After gridding, Fourier transformation, and denoising, 17 the SNR of the area under the curve of each metabolite was measured over the entire organ (brain, kidney, liver, or heart with blood pool). For quantification of apparent [1- 13 C]pyruvate-to-[ 13 C]bicarbonate metabolism (k PB ), a metabolic exchange model was fitted if SNR was > 3.…”
Section: Processing and Analyses Of In Vivo Datamentioning
confidence: 99%
“…The in vivo 13 C data were reconstructed and analyzed in MATLAB (MathWorks). After gridding, Fourier transformation, and denoising, 17 the SNR of the area under the curve of each metabolite was measured over the entire organ (brain, kidney, liver, or heart with blood pool). For quantification of apparent [1- 13 C]pyruvate-to-[ 13 C]bicarbonate metabolism (k PB ), a metabolic exchange model was fitted if SNR was > 3.…”
Section: Processing and Analyses Of In Vivo Datamentioning
confidence: 99%
“…Recent technical advances for HP studies have shown that metabolic quantification could be further improved through specialized acquisition and denoising techniques. [18][19][20][21] These techniques provide improved SNR and finer spatial resolution, enabling better localization of metabolism. In particular, a multi-resolution HP 13 C EPI approach was developed that enables the acquisition of the injected HP 13 C pyruvate at a higher spatial resolution than its metabolic products lactate and bicarbonate with their lower inherent SNR.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [ 23 ] used the HOSVD algorithm super resolution (SR) technology to reconstruct DWI datasets with high discrimination rate and achieved good results, which reflected that the improved HOSVD algorithm had a good effect on DWI image denoising, which was consistent with the results of this work. The HOSVD algorithm has also been applied to other imaging technologies, such as PET [ 24 ], hyperpolarized 13C magnetic resonance image [ 25 ], and CT [ 26 ], all of which have achieved good research results.…”
Section: Discussionmentioning
confidence: 99%